Profiling Genome-Wide DNA Methylation Patterns in Human Aortic and Mitral Valves - Halawa, Sarah (AUC Knowledge Fountain, 2020)
Cardiac valve structure and function are complex and include dynamic interactions between cells, extracellular matrix (ECM) and their hemodynamic environment. Valvular gene expression is tightly regulated by a variety of mechanisms including epigenetic factors such as histone modifications, RNA-based mechanisms and DNA methylation. To date, methylation fingerprints of non-diseased human aortic and mitral valves have not been studied. In this work I analyzed the differential methylation profiles of 12 non-diseased aortic and mitral valve tissue samples (in matched pairs). Methylation data were acquired via reduced representation bisulfite sequencing (RRBS). Of 1601 promoters analyzed genome-wide, my analysis revealed 584 differentially methylated (DM) promoters, of which 13 were reported in endothelial mesenchymal trans-differentiation (EMT), 37 in aortic and mitral valve disease and 7 in ECM remodeling. Both functional classification and network analysis showed that genes associated with the differentially methylated promoters were enriched for WNT-, Cadherin-, Endothelin-, PDGF- and VEGF- signaling implicated in valvular physiology and pathophysiology. Additional enrichment was detected for TGFB-, NOTCH- and Integrin- signaling involved in EMT as well as ECM remodeling. These data provide the first insight into differential regulation of human aortic and mitral valve tissue and identify candidate genes linked to differentially methylated promoters. This work will improve the understanding of valve biology, valve tissue engineering approaches and contributes to the identification of relevant drug targets.